Spatial ecology of copperhead snakes (Agkistrodon contortrix) in response to urban park trails. Issue 1 (19th March 2020) - Carrasco-Harris, Malle F; Bowman, Dale; Reichling, Steve; Cole, Judith A
Abstract: Urban forests and parks are important for recreation and may serve as a natural corridor for commuters. The consequences of human-mediated disturbance in natural areas are documented for avian and mammalian species. Less is known about the consequences of human disturbance on reptile species, specifically snakes, residing in natural refuges within the urban matrix. Thus, we examined the spatial activity of copperheads ( Agkistrodon contortrix ) in regard to pedestrian trails within an urban forest. We used radio telemetry to track snakes during the active season and estimated distances moved in between relocations, distances to the nearest trail and home range size for individuals. We found sex and season, but not distance to the nearest trail, affected the distance snakes moved. In addition, we observed a weak, positive relationship between home range size and average distance to the trail. Sex, season and body condition did not explain snake distance to the trail, but individual patterns were variable for snakes compared to random locations generated from snake relocations. Our study indicates copperheads may be tolerant of low-level human disturbances found in an urban forest. Further work should be done to quantify levels of disturbance, such as trail use, and compare the behavior of reptiles across urban park types and locations.